Trade-offs and synergies between pastoral activities and ecosystem services: Valuation of carbon emissions mitigation strategies in livestock systems - Florez, Fernando; Louhaichi, Mounir; Yigezu, Yigezu Atnafe; Gonzalez Quintero, Ricardo; Notenbaert, An; Wane, Abdrahmane; Burkart, Stefan (2025)
Livestock production is one of the economic enterprises humans engage in for their livelihoods using the natural ecosystem while providing ecosystem services and environmental benefits. Carbon storage and sequestration is an ecosystem service in livestock systems with cultivated forages, rangelands, and agro-silvopastoral systems. While humans, through consumption, put pressure on natural ecosystems, they also develop and introduce policy, institutional, and technological innovations, which have the potential to improve the carbon balance and mitigate climate change. While there is evidence for the technical efficacy of these interventions, the cost of inaction, the investment required for implementing them, their economic viability, and their impacts if implemented at a large scale have yet to be fully known, thereby limiting our ability to promote financing. We aim to formulate a viable method for the economic and social valuation of the benefits of action to implement interventions that enhance carbon balance. For the economic valuation, we employ market pricing methods that consist of consulting carbon prices in the world's main Tradable Emissions Permit Systems and the financial and economic instruments for emissions regulation used in the country where the evaluation is carried out. For the social valuation, we assess the stakeholders' level of knowledge and perception of the topic by using contingent valuation methods, including Discrete Choice Experiments and Public Goods Games, to estimate their willingness to support mitigation strategies financially. We have implemented this strategy in four studies in Colombia and Kenya to evaluate the carbon footprint reduction in beef and milk production. Our findings show favourable outcomes where the environmental value prevented from being lost or newly generated due to interventions surpasses the costs associated with implementing them.